O controle difuso de constitucionalidade como instrumento de tutela do patrimônio cultural no Brasil: um exame sob a ótica da dimensão cultural da sustentabilidade - Finger, Otávio Martins (2024)
This work aimed to demonstrate how judicial review of legislation can be a way of protecting cultural heritage in Brazil. The relevance of the study lies in the rise of constitutional jurisdiction in Brazilian territory recently, especially for the direct defense of fundamental rights. Furthermore, the theme of sustainability, whose cultural dimension is necessary to consider even in judicial decisions, gains relevance. Therefore, a joint revisitation of the themes of judicial review and cultural heritage was carried out, the first being the main aspect of constitutional jurisdiction and the second, a fundamental right of a diffuse nature. The following research problem was thus developed: analyzing concrete cases decided by Brazilian courts, how the judicial review carried out by the Judiciary in this context can constitute an effective instrument for the protection of cultural assets and manifestations, safeguarding the cultural dimension of sustainability? In methodological terms, the deductive approach was used, as the research covered a broad examination of the themes of judicial review and cultural heritage, as well as its most evident aspects, potentialities and problems, such as unconstitutional omission and the application of the regime of intellectual property within the scope of heritage. Finally, a joint treatment of such issues was carried out, with the analysis of specific cases decided by judicial courts. As for the method of procedure, the bibliographic method was chosen, taking into account that the research was developed based on the examination and interpretation of books, scientific articles, journalistic reports, normative texts and especially case law, including the themes of judicial review, cultural dimension of sustainability and protection of cultural heritage in Brazil. As for research techniques, expanded records and summaries were adopted, as well as searching for judicial decisions on official court websites. In this regard, 12 cases were selected from seven Brazilian courts since 2008, coming from higher courts (Supreme Federal Court and Superior Court of Justice) and lower courts (Courts of Justice and Federal Regional Courts). The theoretical and legal basis notably included concepts and considerations from authors such as Luiz Guilherme Marinoni, Ignacy Sachs, Ana Maria Moreira Marchesan and Juliana Santilli. In the end, considering decisions given in the specific cases analyzed, as well as the various issues brought to the Judiciary's consideration, it was possible to infer that the judicial review can constitute an efficient instrument for the protection of Brazilian cultural heritage, and also for democratic access to justice for this purpose, through the selection of strategic disputes. However, it was noticed that there was a lack of consideration of the cultural dimension of sustainability in some cases, which is also evident from the still incipient number of cases in which the issue of judicial review is raised and carried out. Furthermore, in other cases, there was a preference for judicial self-restraint, including through the reform of decisions that are beneficial to cultural heritage.